Avoid using spectrophotometric determination of malondialdehyde as a biomarker of oxidative stress. (6th June 2018) - Khoubnasabjafari, Maryam; Soleymani, Jafar; Jouyban, Abolghasem
Despite wide applications of malondialdehyde as a biomarker of oxidative stress, it possesses a number of characteristics that are against its role as a biomarker. This short communication summarizes these shortcomings and reports some recommendations.